Polskie fundusze inwestujące w nieruchomości - analiza ich działalności i próba oceny - Kowalczyk, Patrycja (Polish Funds Investing in Fixed Properties - Analysis of Their Activity and the Attempt of the Assessment, 2008)
In the last years in Poland there is observed a development of the market of the fixed property, in particular in major urbanized areas. Fixed properties became the alternative form of investment in the relationship to financial instruments. Rate of the return from investment in fixed properties are similar, sometimes even deciding higher than rate of the return get from investment in shares. Funds investing in fixed properties which are more and more large and meaning investors. The aim of this paper is analysis of Polish funds investing in fixed properties and the attempt of the assessment of their activity.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 59-67